Simultaneous screening and detection of pharmaceutical co-crystals by the one-step DSC–FTIR microspectroscopic technique. Issue 4 (April 2017) - Lin, Shan-Yang
Graphical abstract: Highlights: A powerful method combining FTIR microspectroscopy with thermal analysis is introduced. One-step DSC–FTIR technique can simultaneously and directly screen and detect pharmaceutical co-crystal formation. Schematic steps of design, screening and characterization of co-crystal formation have been proposed. This one-step real-time DSC–FTIR technique could be applied at the early stages of co-crystal searching. Abstract : Various methods and analytical techniques for the preparation and identification of pharmaceutical co-crystals have been applied, but these operations require considerable time for the screening and preparation of co-crystals. In this review, a powerful method that combines Fourier-transform infrared (FTIR) microspectroscopy with thermal analysis is introduced. This unique one-step real-time differential scanning calorimetry (DSC)–FTIR microspectroscopic approach has been successfully applied to simultaneously and directly screen and detect pharmaceutical co-crystal formation in systems such as indomethacin–saccharin, indomethacin–nicotinamide, carbamazepine–glutaric-acid, metaxalone–succinic-acid and piroxicam–saccharin. This powerful one-step DSC–FTIR combined technique provides an easy and direct method for one-step screening and qualitative detection of co-crystal formation in real time.